Implementation of the Smart Car Controller System in Cars Based on the Internet of Things - Adhitama, Firnawa; Sejati, Rr Hajar Puji (STKIP Singkawang, 2024)
This research aimed to create innovations in the development of the Internet of Things in car accessories to add system accessories to cars. The type of research used was experimental research. The subjects studied in this research were car users whose hobbies were various types of cars. The use of Internet of Things media in car accessories is very unique and has not been widely used to create innovations in the development of Internet of Things technology. This research aimed to help car users control their cars through the voice control feature, as well as to make car users a second choice to upgrade their car systems compared to buying a sophisticated car at an expensive price. The research results showed that there were still very few car users equipped with control systems compared to luxury car users who had sophisticated systems. Thus, it can be concluded that the idea of a voice control system using the Internet of Things for car accessories could help car users increase the sophistication of the car system and is a good choice.